High resolution MRI guided endovascular intervention of basilar artery disease. (4th March 2011) - Jiang, Wei-Jian; Yu, Wengui; Ma, Ning; Du, Bin; Lou, Xin; Rasmussen, Peter A
Abstract : Background and aim: High resolution MR imaging (HRMRI) has been used to study intracranial atherosclerotic plaques. How HRMRI guided our decision making process in endovascular intervention of basilar artery (BA) atherosclerotic disease is reported. Methods: 3 patients with symptomatic BA atherosclerotic disease underwent BA wall HRMRI under a 3 T MR scanner. Endovascular intervention was then performed utilizing HRMRI findings to guide therapy and to aid in planning the intervention. Results: HRMRI clearly identified the eccentric atherosclerotic plaque at the opposite side of the adjacent right anterior inferior cerebellar artery in one patient and left posterior cerebral artery in one patient, and eccentric atherosclerotic plaque protruding BA lumen at the opposite side of the adjacent right anterior inferior cerebellar artery in the remaining patient. The BA stenosis was stented without compromise of the adjacent branch arteries in the three patients. Conclusion: HRMRI may be used to delineate the eccentric atherosclerotic plaque and the ostia of the major side branches of BA. The HRMRI findings seem helpful in guiding BA stenting with reduced complication risk.